Fenomenologia i performatyka gestu w tańcu współczesnym - Fazan, Teresa (Przestrzenie Teorii, 2019)
The paper covers the problem of gestural expression and the role of the body in the aesthetic experience analysed in the Maurice Merleau-Ponty’s phenomenology of art and Erika Fischer-Lichte’s theory of performance. The author compiles these theorists’ conclusions and contextualizes them in the field of modern and postmodern dance. The ultimate goal is to analyse the artists’ statements in the context of formulated conclusions and syntheses. In summary, the author draws attention to current aesthetic research on dance and pinpoints the benefits of philosophical phenomenological) interest in the modern and postmodern dance.